Sinonasal Tumors - Chiu Alexander G, Suh Jeffrey D, Ramakrishnan Vijay R; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2012)
The purpose of this book is to present a modern way to treat sinonasal tumors with respect to traditional tumor extirpation principles and the need for radical excisions when the indications arise. Sinonasal Tumors provides a comprehensive resource for the management of benign and malignant tumors of the paranasal sinuses. In Sinonasal Tumors, there are many chapters elaborating on some of the scientific advancements in diagnosis such as improved imaging techniques and pathological diagnosis, as well as ample space devoted to the operative technique and adjunctive treatment with radiation and/or chemotherapeutic techniques. Written by experts in a number of fields involved in the care of sinus tumors, practitioners of all levels and in the disciplines of otolaryngology, head and neck surgery, radiation oncology and hematology oncology, will find the most current and updated information within.
Keywords: Otolaryngology; Electronic books